Aktivitas Antibakteri Ekstrak Etanol Daun Tapak Kuda (Ipomoea pes-caprae (L.) R. Br.) terhadap Bakteri Staphylococcus epidermidis - Sri Wahyu Kurnia Putri; Devi Nurhasana; Avidlyandi Avidlyandi; Irfan Gustian; Sipriyadi Sipriyadi; Morina Adfa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to determine the antibacterial activity of the ethanol extract of the leaves of Tapak Kuda (Ipomoea pes-caprae) against Staphylococcus epidermidis. The method used was Kirby-Bauer for the antibacterial test with various concentrations of ethanolic extract of I. pes-caprae leaf extract: 5 mg/mL, 20 mg/mL, 35 mg/mL, and 50 mg/mL, with five replications. The antibiotic clindamycin was used as a positive control, while DMSO was a negative control. The results showed that after 24 hours of incubation, the zone of inhibition of bacterial growth was demonstrated by the experimental and the positive control groups, while the negative control did not show the zone of inhibition. The diameter of the largest inhibition zone (11.40 mm) was at a 50 mg/mL test concentration, which was indicated as a strong category. In conclusion, the ethanolic extract of the leaves of I. pes-caprae can inhibit the growth of S. epidermidis at all test concentrations. Keywords: Antibacterial, Ipomoea pes-caprae, Staphylococcus epidermidis